2022
DOI: 10.1097/01.aoa.0000816720.44866.e3
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetic and Airway Management Practice for Obstetric Surgery in England: A Prospective, Multicenter Observational Study

Abstract: (Anaesthesia. 2021;76:460–471) The use of general anesthesia (GA) in obstetrics is typically avoided due to concerns of increased risks, but is sometimes unavoidable. Accidental awareness during GA (AAGA) has been previously investigated by the Royal College of Anaesthetists and the Association of Anaesthetists in 2013. This study, the direct reporting of awareness in maternity patients (DREAMY) study aimed to determine the incidence, risk factors, and sequelae of AAGA. A secondary study within DREAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…Cormack and Lehane reported that, in the absence of neck pathology (“ rare in obstetric patients ”), the frequency of grades 1, 2, 3 and 4 were 99%, 1%, 1:2000 and < 1:100,000, respectively. This stands in contrast with recent data of obstetric patients undergoing general anaesthesia which reported that the frequency of grades 1, 2, 3 and 4 were 75.6%, 12.3%, 4.7% and 0.3%, respectively [13]. Cormack and Lehane also stated grade‐1 and ‐2 views were not associated with difficult tracheal intubation.…”
Section: Cormack‐lehane: Where We Are Todaycontrasting
confidence: 60%
See 1 more Smart Citation
“…Cormack and Lehane reported that, in the absence of neck pathology (“ rare in obstetric patients ”), the frequency of grades 1, 2, 3 and 4 were 99%, 1%, 1:2000 and < 1:100,000, respectively. This stands in contrast with recent data of obstetric patients undergoing general anaesthesia which reported that the frequency of grades 1, 2, 3 and 4 were 75.6%, 12.3%, 4.7% and 0.3%, respectively [13]. Cormack and Lehane also stated grade‐1 and ‐2 views were not associated with difficult tracheal intubation.…”
Section: Cormack‐lehane: Where We Are Todaycontrasting
confidence: 60%
“…However, in a recent large, prospective observational study of obstetric surgery patients, Odor et al. found Cormack‐Lehane grades 1 and 2a to be associated with 38% of all difficult tracheal intubations [13]. Other data suggest that the incidence of failed tracheal intubation is 1:224, regardless of the grade of view [14].…”
Section: Cormack‐lehane: Where We Are Todaymentioning
confidence: 99%
“…For obstetric surgery, the incidence of AAGA detected by Brice interviews is 1 in 110–152, but these estimates come from studies that are somewhat dated in terms of anaesthetic practice [13, 14] and have not triangulated Brice responses against anaesthetic records and detailed patient reports in the way NAP5 did. Obstetric general anaesthesia for caesarean section involves multiple risk‐factors for AAGA, including the almost universal use of NMB drugs and rapid sequence induction alongside a high incidence of difficult airway management and emergency or out‐of‐hours surgery [15]. It is unclear whether estimated differences in AAGA incidences between obstetric and non‐obstetric surgery can be accounted for solely by the combination of risk‐factors, as is the impact of detection methodology [14].…”
Section: Introductionmentioning
confidence: 99%
“…29 Over the last eight years, the use of propofol has increased. 30,31 The period evaluated in our study ends in December 2016 and is likely to reflect a majority of GAs performed using thiopentone and suxamethonium, though propofol use may have been increasing. There is no evidence of a beneficial effect of propofol over thiopentone on fetal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence of a beneficial effect of propofol over thiopentone on fetal outcomes. 32 The use of opioids during induction of GA has become more common, 31 though any concerns relating to association with adverse neonatal outcomes are not supported by meta-analysis. 33 The use of pre-medication before caesarean section remains unusual in the UK.…”
Section: Discussionmentioning
confidence: 99%